ACCESSIBLE TOURISM: EUROPEAN EXPERIENCE AND UKRAINIAN ASPECTS (INNOVATIVE ECONOMY, 2024)
Danylenko-Kulchytska V.А., Nahara M.B. ACCESSIBLE TOURISM: EUROPEAN EXPERIENCE AND UKRAINIAN ASPECTSPurpose. The aim of the article is to systematize the approaches to defining the concept of “Accessible Tourism” and to develop of a model of accessible tourism for groups of people affected by the war.Methodology of research. The theoretical and methodological bases of the article are the fundamental researches of modern economic theory, scientific works of leading domestic and foreign scientists concerning accessible tourism. The following methods are used in the process of writing the article in order to achieve the goal: theoretical generalization – to highlight the general features of the accessible tourism concept; monographic and systematic analysis – to substantiate the features and advantages of accessible tourism; abstract and logical – to develop the model of accessible tourism; graphic – for visual presentation of the research results.Findings. It is substantiated that that accessible tourism is a transformative approach aimed at ensuring equal opportunities and access to travel for people with different types of disabilities, including physical, intellectual and sensory limitations.It is determined that accessible tourism is part of an inclusive environment and consists of the following elements: universal design; adaptive technologies; inclusive communications; barrier-free infrastructure. It is established that accessible tourism includes a set of principles, methods and tools, logically interconnected and integrated into an inclusive environment in order to ensure equal opportunities and comfort for all tourists.Originality. The model of accessible tourism for war-affected population groups is developed. This model can become the basis for the integration of domestic tourism into the environment of European accessible tourism.Practical value. The main directions of the article make it possible to increase the relevance of management decisions in the process of implementing the principles of accessible tourism at hospitality enterprises.Key words: barrier-free environment, accessible tourism, hospitality company, universal design, inclusive technologies, social integration.
Keywords: barrier-free environment; accessible tourism; hospitality company; universal design; inclusive technologies; social integration.